Ferroptosis induced by environmental pollutants and its health implications - Fu-Han Gong; Liyuan Liu; Xuesheng Wang; Qi Xiang; Xin Yi; Ding-Sheng Jiang (Cell Death Discovery)
Abstract Environmental pollution represents a significant public health concern, with the potential health risks associated with environmental pollutants receiving considerable attention over an extended period. In recent years, a substantial body of research has been dedicated to this topic. Since the discovery of ferroptosis, an iron-dependent programmed cell death typically characterized by lipid peroxidation, in 2012, there have been significant advances in the study of its role and mechanism in various diseases. A growing number of recent studies have also demonstrated the involvement of ferroptosis in the damage caused to the organism by environmental pollutants, and the molecular mechanisms involved have been partially elucidated. The targeting of ferroptosis has been demonstrated to be an effective means of ameliorating the health damage caused by PM2.5, organic and inorganic pollutants, and ionizing radiation. This review begins by providing a summary of the most recent and important advances in ferroptosis. It then proceeds to offer a critical analysis of the health effects and molecular mechanisms of ferroptosis induced by various environmental pollutants. Furthermore, as is the case with all rapidly evolving research areas, there are numerous unanswered questions and challenges pertaining to environmental pollutant-induced ferroptosis, which we discuss in this review in an attempt to provide some directions and clues for future research in this field.